Demonstration of Dose-Dependent Global and Regional Cocaine-Induced Reductions in Brain Blood Flow Using a Novel Approach to Quantitative Single Photon Emission Computerized Tomography - Johnson, M.D., Ph.D, Bankole; Lamki, M.D, Lamk; Fang, M.S, Bing; Barron, M.D, Bruce; Wagner, Ph.D, Louis; Wells, M.D, Lynda; Kenny, M.D, Paul; Overton, M.D, Dennis; Dhother, M.D, Sukhjindar; Abramson, M.D, David; Chen, Ph.D, Richard; Kramer, M.D, Larry (Neuropsychopharmacology (New York, N.Y.), 1998)
Ischemic stroke is a common cause of morbidity and mortality in cocaine addicts. Because the previous semiquantitative single photon emission computerized tomography (SPECT) method for measuring brain blood flow does not quantify blood flow, the magnitude and specificity of cocaine’s effects during drug taking has not been well established. Here, using a novel quantitative approach to SPECT, we established that intravenous cocaine administration to nine recently abstinent cocaine-dependent subjects was associated with significant decreases in global and regional brain blood flow to dopamine-rich areas such as the prefrontal, frontal, temporal, and subcortical gray matter. Establishing the utility of this relatively new quantitative SPECT technique provides an important tool for the management of vascular disorders of the brain. Additionally, identifying the site-specific effects of cocaine provides targets for the development of putative therapeutic medications to attenuate or minimize ischemic stroke in cocaine addicts.